Coming of Age in Nature: An Ecocritical Reading of Ruskin Bond’s The Room on the Roof - Divya Shikhar (International Journal of Trends in Humanities, 2024)
This research paper explores the human-nature relationship in Ruskin Bond's classic novel, "The Room on the Roof," through the lens of ecocriticism. Ecocriticism, a critical theory examining literature's portrayal of the environment, provides a valuable framework for analyzing the novel's themes of escape, self-discovery, and the impact of human actions on the natural world. The paper analyzes the novel, demonstrating how Bond utilizes ecocriticism to depict the transformative power of nature and the yearning for a more harmonious relationship with the environment. The analysis reveals a constant contrast between the stifling confines of Mr. Harrison's house and the beckoning beauty of the Himalayas. The middle part deepens this contrast, showcasing the regenerative power of the mountains and the potential for sustainable living practices in the Himalayas, while also highlighting the environmental impact of the bustling Dehradun bazaar. Finally, the open-ended conclusion leaves room for interpretation, emphasizing the enduring allure of nature for Rusty and the ongoing challenge of balancing human desires with ecological responsibility. By analyzing the novel's settings, characters, and interactions with the natural world, the paper demonstrates how Bond utilizes ecocriticism to depict the transformative power of nature and the yearning for a more harmonious relationship with the environment. The analysis also sheds light on the complexities of maintaining this connection in a world with competing demands and societal expectations. Overall, the paper argues that "The Room on the Roof" serves as a valuable literary contribution to ecocritical discourse, offering a timeless exploration of the interconnectedness of humans and the natural world.
Keywords: Coming of age; Ecocriticism; Man; Nature; Ruskin Bond; Self-Discovery